Pentingnya Peran Quality Control Independen dalam Pembuatan NOTAM di PIA Wilayah Jakarta - Denisyha Anindhita Syavitri; Rohmah, KyKy; Muzaki, Faizal (Jurnal Bisnis dan Operasi Penerbangan, 2025)
NOTAM (Notice to Airmen) is an important part of aviation safety because it provides important information to pilots and flight operators about conditions, changes and closures of aviation facilities that can affect flight safety. The research method used is a qualitative research method where the researcher conducts a study of group culture in natural conditions through observation and interviews. Therefore, the role of Independent Quality Control is important to avoid NOTAM non-conformities occurring again. To improve the quality of AIS products, especially NOTAMs in AIS Jakarta Region, the role of independent Quality Control to prevent recurrence of NOTAM non-conformities is very important.